ZAPPING THE ELUSIVE CULPRIT - Yam, Herng Pin; Lee, Siow Ping; Tong, Chin Voon (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Hypoglycaemia among patients without diabetes is uncommon and warrants further investigation especially when Whipple’s triad is fulfilled. Endocrine causes of hypoglycaemia include cortisol deficiency and endogenous hyperinsulinemia. We report the case of a 69-year-old female whose insulinoma was unmasked after cessation of glucocorticoids and subsequent management. CASE Our patient is a 69-year-old Malay female who has long standing pemphigus vulgaris (PV) since 1994 treated with oral Prednisolone. With her PV controlled, prednisolone was gradually tapered to 5 mg per week. While on weekly prednisolone, she started to experience severe symptoms of hypoglycaemia. Cosyntropin stimulation test showed a good response which excluded adrenal insufficiency as the cause of hypoglycaemia. Prolonged fasting test showed that she had endogenous hyperinsulinaemic hypoglycaemia. C-peptide was 348 pmol/l with insulin of 3 miu/l while fasting blood sugar was 1.7 mmol/l. Liver function testsand renal profile were normal. Computed Tomography (CT) Scan and Magnetic Resonance Imaging (MRI) of the pancreas, and Endoscopic ultrasound (EUS) and Gallium-68 Dotatate PET/CT scan showed the presence of two pancreatic lesions at the head and tail of the pancreas. Fine needle aspiration cytology (FNAC)during EUS showed that the tail lesion was a Grade 1 neuroendocrine tumour. However, samples from the head lesion were unsatisfactory. Arterial stimulation and venous sampling (ASVS) confirmed that the lesion at the pancreatic tail was an insulin-secreting lesion. Oral diaxozide 100 mg twice daily was not tolerated due to bothersome leg oedema. Subsequently, hypoglycaemia resolved with successful RFA (Radio frequency ablation) of both lesions. CONCLUSION Hypoglycaemia caused by insulinoma can be masked with the use of glucocorticoids. Localization of insulinoma often requires multiple imaging, dynamic studies, and a multidisciplinary approach. RFA via EUS is a safe, minimally invasive, and effective technique for the treatment of insulinoma.